Pengaruh good corporate governance terhadap kinerja keuangan perusahaan perbankan periode 2017-2020 - Maridkha, Antin; Himmati, Risdiana (Nur Science Institute, 2021)
Good Corporate Governance is the foundation that can make business conditions healthier to grow competence in the business sector and eliminate bribery and corruption cases. The objective-based of this research is to determine the effect of Good Corporate Governance (GCG) on the financial performance of banking companies. The population of this study was 12 companies for four periods, a sample of 44 observational data and data obtained from the IDX official website. The analytical method used is panel data regression. The results of this study indicate that institutional ownership, the board of directors, and the audit board have no significant effect on ROA. Meanwhile, institutional ownership has a significant effect on ROE. The board of directors and the audit committee do not significantly affect ROE. The application of Good Corporate Governance (GCG) in companies to generate profits using ROA and ROE profitability measures does not always affect the company's capacity to generate profits.